TEACHING WRITING IN RECOUNT TEXT BY USING CLUSTERING TECHNIQUE - Wardani, Pratiwi Kusuma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThis research is teaching writing recount text by using clustering technique on the eighth grade students of SMP N 8 Pontianak in Academic Year 2016/2017. The research question were â€œdoes the use of clustering technique affect significantly in writing recount text on the eighth grade students of SMP N 8 Pontianak and if does what is the effect.â€ . The method of the research is experimental research and use pre-experimental research design with the sample of 32 students who were eighth grade â€œVIII Bâ€ of SMP N 8 Pontianak in academic year 2016/2017.The research findings showed that there was improvement on students achievement in writing recount text. Based on the result, there is different significant different studentsâ€™ achievement. The mean core of pre-test was 61.17 while the post-test was 77.34. The studentsâ€™ achievement was improved by different score between pre-test and post-test was 16.17. The t-test score (9.51) was higher than t-table (2.040)Â  at degree of freedom (df) = N1 (32-1=31) and the result of the effect size is 1.7 where the category is strong effect. TheÂ  null hypothesis (Ho) was rejected. Because t-value > t-table (9,51 > 2,040) on the level of significance 0,05 and the alternative hypothesis (Ha) was acceptedÂ Keywords : clustering technique, writing, recount text, SMP N 8 Pontianak.Â